The wake asymmetry of an airfoil with a Gurney flap and their connection with the observed lift increase - Boldes, Ulfilas (2010)
The present research analyzes the asymmetry in the rolling up shear layers downstream the blunt trailing edge of airfoils with Gurney flaps as a lift enhancing mechanism. Experimental investigations relating the asymmetry of the vortex flow in the near wake region, able to distort the flow increasing the downwash of an airfoil, have been performed. We examine the lift behaviour and near wake region characteristics of the low Reynolds number airfoil HQ17 without and with Gurney mini-flaps of different lengths. The flow immediately downstream the trailing edge down to 2 mini-flap lengths is explored in order to identify signs of asymmetry of the initial counter rotating vortex structures. Experimental evidence is presented showing that for typical lifting conditions the shear layer rollup process within the near wake is different for the upper and lower vortices: the shear layer separating from the pressure side of the airfoil begins its rollup immediately behind the trailing edge creating a stronger vortex while the shear layer from the suction side begins its rollup more downstream creating a weaker vortex. Aspects of a mechanism connecting the different evolution and pattern of these initial vortex structures with the lift increase due to these flaps are presented.